ISSR markers and morphometry determine genetic diversity and population structure in Hedera helix L. - Abdul Shakoor; Gul Zaib; Fang Zhao; Wuyang Li; Xincan Lan; Somayeh Esfandani-Bozchaloyi (Czech Journal of Genetics and Plant Breeding, 2022)
The article was retracted by the authors based on detected errors in the data processing.